Trapping cell spheroids and organoids using digital acoustofluidics. (29th June 2020) - Cai, Hongwei; Wu, Zhuhao; Ao, Zheng; Nunez, Asael; Chen, Bin; Jiang, Lei; Bondesson, Maria; Guo, Feng
Abstract: The precise positioning and arrangement of cell spheroids and organoids are critical to reconstructing complex tissue architecture for tissue engineering and regenerative medicine. Here, we present a digital acoustofluidic method to manipulate cell spheroids and organoids with unprecedented dexterity. By introducing localized vibrations via a C-shaped integrated digital transducer (IDT), we can generate a trapping node to immobilize cell spheroids with a diameters ranging from 20 μ m to 300 μ m. Moreover, we digitally trapped multiple cell spheroids atop the C-shaped IDTs within a closed or open microfluidic chamber. By programming the trapping nodes within a 3 × 3 C-shaped IDT array, we can precisely position cell spheroids into designed patterns. We also demonstrated that our digital acoustofluidic device can accurately control the interaction of spheroid cells and organoids. Along with a simple fabrication procedure and setup, our digital acoustofluidic method can provide precisely manipulate and position various cell spheroids or organoids in a contactless, label-free, and highly biocompatible manner. We believe this technology can be widely used for tissue engineering, regenerative medicine, and fundamental cell biology research.